Monarch Habitat in Conservation Grasslands - Lukens, Laura; Kasten, Kyle; Stenoien, Carl; Cariveau, Alison; Caldwell, Wendy; Oberhauser, Karen (Frontiers in Ecology and Evolution, 2020)
There is strong evidence that a major driver of the decline of eastern North American monarch butterflies (Danaus plexippus) is the loss of breeding habitat in the upper midwestern United States. Grasslands, including conservation areas, provide some of the largest remaining tracts of breeding habitat available to monarchs. While grassland conservation has been well-studied, little is known about how monarchs interact with these areas, or how planting and management practices impact the quality of the habitat for monarchs. Here, we evaluate monarch habitat and use by monarchs in 61 conservation grasslands (including restoration sites in the U.S. Department of Agriculture Conservation Reserve Program, U.S. Fish and Wildlife Service Partners for Fish and Wildlife Program, and privately-funded restored prairies) in Minnesota, Wisconsin, and Iowa. We documented milkweed (Asclepias spp.) density and diversity, blooming plant frequency and richness, and immature monarch density during the monarch breeding seasons of 2016 and 2017, along with seeding and management histories. Milkweed was observed at 60 of 61 study sites with a mean density of 1,390 plants per hectare (median=783), a greater density than previously estimated in conservation grasslands. Monarchs were observed at 57 of 61 sites. Asclepias syriaca was the most frequently observed species, regardless of whether it was planted. Asclepias tuberosa and Asclepias incarnata may be the most cost-effective milkweeds to seed in our study geography, given that they were both more likely to be present and occurred at higher densities when planted than when not planted. Forb establishment rate varied across species planted and seeding rates. Increased rates of forb establishment were observed at larger sites, sites planted in the fall, and sites with fewer species in the seed mix. We observed a relatively low frequency of early-season nectar sources, suggesting that managers should consider including more early-blooming species in seed mixes and on existing conservation lands. We present establishment information for consideration in seed mix design and describe how our findings can be used to inform monarch habitat availability models, future studies, and conservation efforts.